Apropriação de gêneros e discursos publicitários: como a publicidade e as blogueiras construíram relações consensuais na interação com as leitoras nos blogs de moda feminina - Campos, Laís Tolentino Muniz (2016)
The field of advertising has undergone speech changes since the first records to the arrival of the Internet. In cyberculture, the advertising experienced changes in the issuer pole and ceased to be the only one to produce content and communication have new voices. The Segmentation and public saturation stimulated by the appearance of different communication devices led advertising to meet the needs of individual consumers, informed by communications technol-ogy, and went on to determine the strategies of advertisers in digital environments frequented by him. With increasing audience of fashion blogging, the collaboration, the sharing and the recommendation were redirected and blogs began to incorporate the interests of the market and consumer publications sponsored by advertising. In this sense, the discourse of fashion bloggers, not translated anymore personal experiences and integrated the goals of advertisers. This study aimed to identify how advertising appropriates the genres of fashion blogs, as bloggers have adopted the language of advertising in their publications and how this dual ownership has changed the relationship between bloggers and readers. With the support of discourse analysis method, we identified how advertising is inserted in the genres of fashion blogs, allowing bloggers adopt the language of advertising and use routinely in publications. We also analyze how this dual process interfered with social relations between bloggers and readers and how these relationships are established in the comments of the publications. Keywords: Fashion blogs. Genres. Advertising Language. Bloggers. Readers. Interactions.